Methods of organizing the preliminary selection of projects and works in the business portfolio of a multidisciplinary enterprise - Bolebrukh, O.; Chupryna, Iu.; Rovenskyy , A. (Ways to Improve Construction Efficiency, 2020)
A review of the structural and functional model of development and an analysis of market conditions that are taken into account when choosing a project based on a group of influencing factors when choosing project options. The necessity of the analysis of the basic indicators concerning management of a subject area of ​​the project, management of cost, time management, and other component functions of management of the project of development is defined. From the standpoint of the structural approach, the real estate market is analyzed and classified by indices of value, price expectations, etc. It is revealed that the method of distribution of funds from the regional development fund, based on the analysis of a number of indicators of the region, the main of which are industrial output, budget and financial security, the ratio of per capita income and subsistence level, social structure, social security. and engineering infrastructure. The method of the list of criteria concerning the method of selection of projects for realization which consists in conformity of indicators of the project to each criterion is investigated, and on each criterion the expert estimation is given. The method allows to analyze all the advantages and disadvantages of the evaluated projects and ensures that none of the criteria will be forgotten, even if there are difficulties with the initial evaluation or with the formalization of the data. The developed mechanism influencing the project implementation allows to select in the portfolio such projects that are highly likely to be successfully implemented by the enterprise, and will really improve the internal processes at the enterprise and increase its competitiveness in the future, ie the portfolio is not just focused on in the near future, it aims to increase competitiveness in the long run. The advantages for companies that use the developed tools are to increase competitiveness based on accurate calculation of economic indicators of projects, ensuring a clear relationship between current project activities and management of enterprise strategy (due to concentration on strategic goals), use of strengths of internal development. the environment of the enterprise and the leveling of the weak (due to the importance of projects to improve business processes of the enterprise).